Studi Korelasional : Kepuasan Kerja Dan Motivasi Kerja Dengan Komitmen Organisasi Pada Guru Smp Budi Agung Jakarta - Farid Fauzi (Proceedings of Annual Conference on Islamic Educational Management, 2021)
This study discusses the correlation between the variables of job satisfaction (X1) and work motivation (X2) with organizational commitment (Y) at Budi Agung Junior High School Jakarta with a sample of 23 teachers. Based on the results of the study, there are several significant correlations 1) there is a positive and significant correlation between (X1) and the variable (Y), ry1 has a correlation value of 0.750 and a coefficient of determination of 0.563 which means that 56.30% of the variance occurs in the variable (Y). ) can be explained in the variance of the variable (X1) 2) There is a positive and significant correlation between the variable (X2) and the variable (Y), ry2 has a correlation coefficient value of 0.899 and a coefficient of determination value of 0.808 or 80.80% of the variance contained in variable (Y) can be explained through variable (X2) 3) there is a positive and significant correlation between variables (X1) and (X2) together with variable (Y), the correlation coefficient ry1,2 is 0.913 and the coefficient of determination is 0.834 which means that 83.40% of the variance in the variable (Y) can be explained by the variance of the variables (X1) and (X2) together. So it can be concluded that there is a significant correlation between the variables of job satisfaction and work motivation with organizational commitment both jointly and between variables on teachers at Budi Agung Junior High School Jakarta.